5
$\begingroup$

Let $n\ge 2$ be postive integer and $a_{i},(i=1,2,\cdots,n)$ be real numbers such that $a_{i}>1,(i=1,2,\cdots,n),\prod_{i=1}^{n}(a_{i}-1)=1$. Show that $$\sum_{i=1}^{n}\dfrac{1}{\displaystyle\sum_{k=1}^{n-1}ka_{i+k-1}}\le\dfrac{1}{n-1}$$ where $a_{n+m}=a_{m},\forall m\ge 1$

It seem use AM-GM inequality. I have try all methods can't solve this problem.

$$\sum_{k=1}^{n-1}ka_{i+k-1}=a_{i}+2a_{i+2}+3a_{i+3}+\cdots+(n-1)a_{i+n-1-1}$$ $$\sum_{i=1}^{n}\dfrac{1}{\displaystyle\sum_{k=1}^{n-1}ka_{i+k-1}}=\sum_{i=1}^{n}\dfrac{1}{a_{i}+2a_{i+2}+3a_{i+3}+\cdots+(n-1)a_{i+n-1-1}}\le\dfrac{1}{n-1}$$

$\endgroup$
  • $\begingroup$ Wait, for $i=4$ we get that $a_{i+n-1-1} = a_{n+2}$, something doesnt seem right, since we only have $n$ variables? $\endgroup$ – cirpis Aug 18 '17 at 14:39
  • $\begingroup$ $a_{n+2}=a_{2}$ $\endgroup$ – function sug Aug 18 '17 at 14:50
  • $\begingroup$ Ah, missed that, thanks! $\endgroup$ – cirpis Aug 18 '17 at 14:54
  • $\begingroup$ This is work in progress, a quick brainstorming shows that $$\sum_{k=1}^{n−1}ka_{i+k−1}=a_i+2a_{i+2}+3a_{i+3}+...+(n−1)a_{i+n−1−1}>1+2+3+...+n-1=\frac{n(n-1)}{2}$$ or $$\frac{1}{\sum\limits_{k=1}^{n−1}ka_{i+k−1}}<\frac{2}{n(n-1)}$$ and $$\sum\limits_{i=1}^{n}\frac{1}{\sum\limits_{k=1}^{n−1}ka_{i+k−1}}<\frac{2n}{n(n-1)}=\frac{2}{n-1}$$ Question is, how does $\prod\limits_{i=1}^{n}(a_i−1)=1$ improve it? $\endgroup$ – rtybase Aug 20 '17 at 15:22
4
+50
$\begingroup$

This problem was proposed by Dmitriy Maximov on XXIV Russian Festival of Math Youth. Here is the official solution.

Denote $a_k^{n-1}=x_k-1$. The product of new positive variables $a_i$ equals 1. Consider the denominator of the first fraction: \begin{align*} x_1+2x_2+3x_3+ \ldots +(n-1)x_{n-1}&=a_1^{n-1}+2a_2^{n-1}+ \ldots (n-1)a_{n-1}^{n-1}+ 1+2+\ldots+(n-1)= \\ =(n-1)+\bigl(a_{n-1}^{n-1}+(n-2)\bigr)&+\bigl(a_{n-1}^{n-1}+a_{n-2}^{n-1}+(n-3)\bigr)+ \bigl(a_{n-1}^{n-1}+a_{n-2}^{n-1}+a_{n-3}^{n-3}+(n-4)\bigr)+\\ \ldots+ & \bigl(a_{n-1}^{n-1}+a_{n-2}^{n-1}+\ldots+a_1^{n-1}\bigr). \end{align*} Now we estimate all summands (except the first) by AM-GM for $n-1$ numbers (some of them equal to 1). This makes denominators lesser, thus fractions greater. The denominator of the first fraction becomes $$ (n-1)a_{n-1}+(n-1)a_{n-1}a_{n-2}+(n-1)a_{n-1}a_{n-2}a_{n-3}+\ldots+(n-1)a_{n-1}a_{n-2}\ldots a_{1}+(n-1). $$ Now it suffices to prove that the cyclic sum of the fractions $$ \frac{1}{a_{n-1}+a_{n-1}a_{n-2}+\ldots+a_{n-1}a_{n-2}\ldots a_1+1} $$ does not exceed 1. Actually this sum equals 1. For proving this we multiply the second fraction by $a_{n-1}a_{n-2} \ldots a_1$ (I mean, multiply both the numerator and denominator), the third by $a_{n-2}a_{n-3} \ldots a_1$ and so on (the last fraction by $a_1$). The denominators become equal, and the sum of numerators becomes equal to the denominator.

$\endgroup$
  • $\begingroup$ Nice,Thank you,and I ask it which year,I can't search it,can you give thik links?Thanks $\endgroup$ – function sug Aug 21 '17 at 12:01
  • 1
    $\begingroup$ the problems in Russian may be found on www.guas.info $\endgroup$ – Fedor Petrov Aug 21 '17 at 12:11
4
$\begingroup$

Let $a_i-1=x_i$.

Thus, $\prod\limits_{i=1}^nx_i=1$ and we need to prove that $$\sum_{i=1}^n\frac{1}{\sum\limits_{k=1}^{n-1}ka_{i+k-1}}\leq\frac{1}{n-1}$$ or $$\sum_{cyc}\frac{1}{a_1+2a_2+3a_3+...+(n-1)a_{n-1}}\leq\frac{1}{n-1}$$ or $$\sum_{cyc}\frac{1}{x_1+2x_2+3x_3+...+(n-1)x_{n-1}+1+2+3+...+(n-1)}\leq\frac{1}{n-1}$$ or $$\sum_{cyc}\frac{1}{x_1+2x_2+3x_3+...+(n-1)x_{n-1}+\frac{n(n-1)}{2}}\leq\frac{1}{n-1}$$ or $$\sum_{cyc}\left(\frac{1}{x_1+2x_2+3x_3+...+(n-1)x_{n-1}+\frac{n(n-1)}{2}}-\frac{1}{\frac{n(n-1)}{2}}\right)\leq\frac{1}{n-1}-\frac{2}{n-1}$$ or $$\sum_{cyc}\frac{x_1+2x_2+3x_3+...+(n-1)x_{n-1}}{x_1+2x_2+3x_3+...+(n-1)x_{n-1}+\frac{n(n-1)}{2}}\geq\frac{n}{2}.$$ Now, by C-S $$\sum_{cyc}\frac{x_1+2x_2+3x_3+...+(n-1)x_{n-1}}{x_1+2x_2+3x_3+...+(n-1)x_{n-1}+\frac{n(n-1)}{2}}=$$ $$\sum_{i=1}^n\frac{\sum\limits_{k=1}^{n-1}kx_{i+k-1}}{\sum\limits_{k=1}^{n-1}kx_{i+k-1}+\frac{n(n-1)}{2}}=\sum_{i=1}^n\frac{\left(\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)^2}{\left(\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)^2+\frac{n(n-1)}{2}\cdot\sum\limits_{k=1}^{n-1}kx_{i+k-1}}\geq$$ $$\geq\frac{\left(\sum\limits_{i=1}^n\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)^2}{\sum\limits_{i=1}^n\left(\left(\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)^2+\frac{n(n-1)}{2}\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)}=$$ $$=\frac{\frac{n^2(n-1)^2}{4}\sum\limits_{i=1}^nx_i}{\sum\limits_{i=1}^n\left(\left(\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)^2+\frac{n(n-1)}{2}\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)}.$$ Thus, it remains to prove that $$\frac{n(n-1)^2}{2}\sum\limits_{i=1}^nx_i\geq\sum\limits_{i=1}^n\left(\left(\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)^2+\frac{n(n-1)}{2}\sum\limits_{k=1}^{n-1}kx_{i+k-1}\right)$$ or $$\frac{n(n-1)^2}{2}\sum\limits_{i=1}^nx_i\geq\sum\limits_{i=1}^n\left(\sum\limits_{k=1}^{n-1}ka_{i+k-1}\right)^2+\frac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k.$$ But $$\sum\limits_{i=1}^n\left(\sum\limits_{k=1}^{n-1}ka_{i+k-1}\right)^2=\sum_{cyc}(x_1+2x_2+3x_3+...+(n-1)x_{n-1})^2=$$ $$=\sum_{cyc}\left(x_1^2+2^2x_2^2+...+(n-1)^2x_{n-1}^2\right)+2\sum_{cyc}\sum_{1\leq j<k\leq n-1}jkx_jx_k=$$ $$=(1^2+2^2+...+(n-1)^2)\sum_{i=1}^nx_i^2+2\sum_{cyc}\sum_{1\leq j<k\leq n-1}jkx_jx_k=$$ $$=\frac{(n-1)n(2n-1)}{6}\sum_{i=1}^nx_i^2+2\sum_{cyc}\sum_{1\leq j<k\leq n-1}jkx_jx_k.$$ Hence, we need to prove that $$\tfrac{n(n-1)^2}{2}\sum_{i=1}^nx_i^2+n(n-1)^2\sum_{1\leq j<k\leq n}x_jx_k\geq$$ $$\geq\tfrac{(n-1)n(2n-1)}{6}\sum_{i=1}^nx_i^2+2\sum_{cyc}\sum_{1\leq j<k\leq n-1}jkx_jx_k+\frac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k$$ or $$\left(\tfrac{n(n-1)^2}{2}-\tfrac{(n-1)n(2n-1)}{6}\right)\sum_{i=1}^nx_i^2+n(n-1)^2\sum_{1\leq j<k\leq n}x_jx_k\geq$$ $$\geq2\sum_{cyc}\sum_{1\leq j<k\leq n-1}jkx_jx_k+\frac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k$$ or $$\frac{n(n-1)(n-2)}{6}\sum_{i=1}^nx_i^2+n(n-1)^2\sum_{1\leq j<k\leq n}x_jx_k\geq$$ $$\geq2\sum_{cyc}\sum_{1\leq j<k\leq n-1}jkx_jx_k+\frac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k.$$ Now, $$\sum\limits_{cyc}\sum\limits_{1\leq j<k\leq n-1}jkx_jx_k=\sum_{cyc}\sum i(i+1)x_ix_{i+1}+\sum_{cyc}\sum i(i+2)x_ix_{i+2}+...=$$ $$=A_1\sum_{cyc}x_1x_2+A_2\sum_{cyc}x_1x_3+...$$ and by Rearrangement $A_1$ is a maximal coefficient between all coefficients $A_k$,

which says that in the left side the coefficient before $\sum\limits_{cyc}x_1x_2$,

which is $n(n-1)^2-2A_1$, will be minimal.

For the rest expressions we can use AM-GM: $$(2A_1-2A_2)\sum_{cyc}x_1x_3+ (2A_1-2A_3)\sum_{cyc}x_1x_4+...\geq K,$$ where the value of $K$ we'll get a bit of later.

Thus, it's enough to prove that $$\frac{n(n-1)(n-2)}{6}\sum_{i=1}^nx_i^2+\left(n(n-1)^2-2A_1\right)\sum_{1\leq j<k\leq n}x_jx_k+K\geq\frac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k.$$ Now, $$A_1=1\cdot2+2\cdot3+...+(n-2)(n-1)=\sum_{k=1}^{n-2}k(k+1)=$$ $$=\frac{(n-2)(n-1)(2n-3)}{6}+\frac{(n-2)(n-1)}{2}=\frac{n(n-1)(n-2)}{3}.$$ Thus, it's enough to prove that: $$\tfrac{n(n-1)(n-2)}{6}\sum_{i=1}^nx_i^2+\left(n(n-1)^2-\tfrac{2n(n-1)(n-2)}{3}\right)\sum_{1\leq j<k\leq n}x_jx_k+K\geq\tfrac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k$$ or $$\tfrac{n(n-1)(n-2)}{6}\sum_{i=1}^nx_i^2+\tfrac{n(n-1)(n+1)}{3}\sum_{1\leq j<k\leq n}x_jx_k+K\geq\tfrac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k.$$ Now, we can get a value of $K$.

Indeed, the equality in the original inequality occurs for $x_1=x_2=...=x_n=1$ and AM-GM saves this thing.

Thus, $$K=\frac{n^2(n-1)^2}{4}\cdot n-\frac{n(n-1)(n-2)}{6}\cdot n-\frac{n(n-1)(n+1)}{3}\cdot\frac{n(n-1)}{2}=$$ $$=\frac{n^2(n-1)(n-2)(n-3)}{12}.$$ Id est, we need to prove that: $$\tfrac{n(n-1)(n-2)}{6}\sum_{i=1}^nx_i^2+\tfrac{n(n-1)(n+1)}{3}\sum_{1\leq j<k\leq n}x_jx_k+\tfrac{n^2(n-1)(n-2)(n-3)}{12}\geq\tfrac{n^2(n-1)^2}{4}\sum\limits_{k=1}^{n}x_k$$ or $$2(n-2)\sum_{i=1}^nx_i^2+4(n+1)\sum_{1\leq j<k\leq n}x_jx_k+n(n-2)(n-3)\geq3n(n-1)\sum\limits_{k=1}^{n}x_k.$$ Now, let $\sum\limits_{i=1}^nx_i=nu$, $\sum\limits_{1\leq i<j\leq n}x_ix_j=\frac{n(n-1)}{2}v^2$, where $v>0$,

$\sum\limits_{1\leq i<j<k\leq n}x_ix_jx_k=\frac{n(n-1)(n-2)}{6}w^3$ and $\prod\limits_{i=1}^nx_i=t^n$, where $t>0$.

Thus, $u\geq v\geq w\geq t$ and we need to prove that $$2(n-2)(n^2u^2-n(n-1)v^2)+4(n+1)\cdot\tfrac{n(n-1)}{2}v^2+n(n-2)(n-3)t^2\geq3n(n-1)\cdot nut$$ or $f(t)\geq0$, where $$f(t)=2(n-2)(nu^2-(n-1)v^2)+2(n^2-1)v^2+(n-2)(n-3)t^2-3n(n-1)ut.$$ But $$f'(t)=2(n-2)(n-3)t-3n(n-1)u\leq u(2n^2-10n+12-3n^2+3n)=u(-n^2-7n+12)\leq0,$$ which says $$f(t)\geq f(v)=$$ $$=2(n-2)(nu^2-(n-1)v^2)+2(n^2-1)v^2+(n-2)(n-3)v^2-3n(n-1)uv=$$ $$=(u-v)(2(n-2)u-(n+1)v),$$ which says that for $$2(n-2)-(n+1)\geq0$$ or $$n\geq5$$ our inequality is proven.

Thus, it remains to prove our inequality for $n\in\{2,3,4\}$.

The proof for $n=4$.

We need to prove that $$8u^2+9v^2+t^2\geq18ut$$ and since $t\leq w$, it's enough to prove that $$8u^2+9v^2+w^2-18uw\geq0.$$ Now, $x_1$, $x_2$, $x_3$ and $x_4$ are positive roots of the equation $$(x-x_1)(x-x_2)(x-x_3)(x-x_4)=0$$ or $$x_4-4ux^3+4v^2x^2-w^3x+t^4=0.$$ Thus, by Rolle the following equation $$(x_4-4ux^3+4v^2x^2-w^3x+t^4)'=0$$ or $$x^3-3ux^2+3v^2-w^3=0$$ has three positive roots.

Thus, there are positives $a$, $b$ and $c$ for which $3u=a+b+c$, $ab+ac+bc=3v^2$ and $abc=w^3$,

which says that it's enough to prove $$8u^2+9v^2+w^2-18uw\geq0$$ for all positives $a$, $b$ and $c$.

But this inequality is a linear inequality of $v^2$, which says that it remains to prove the last inequality for an extremal value (even for a minimal value in our case) of $v^2$, which happens for equality case of two variables.

Since the last inequality is homogeneous, we can assume $b=c=1$ and for $a=t^3$ we need to prove that $$\frac{8(t^3+2)^2}{9}+3(2t^3+1)+t^2-6(t^3+2)t\geq0$$ or $$(t-1)^2(8t^4+16t^3-30t^2+10t+59)\geq0,$$ which is obvious.

The proof for $n=3$.

We need to prove that $$a^2+b^2+c^2+8(ab+ac+bc)-9(a+b+c)\geq0$$ for positives $a$, $b$ and $c$ such that $abc=1$.

But this inequality is a linear inequality of $v^2$ again, which says that it's enough to prove the last inequality for $b=a$ and $c=\frac{1}{a^2}$, which gives $$(a-1)^2(10a^4+2a^3-6a^2+2a+1)\geq0,$$ which is obvious.

For $n=2$ the starting inequality it's just equality.

Done!

$\endgroup$
  • $\begingroup$ For n=4 and n=3 have other methods to solve it? Thanks $\endgroup$ – function sug Aug 20 '17 at 23:33
  • $\begingroup$ @function sug I think Mixing Variables method can help, but it's not so nice. $\endgroup$ – Michael Rozenberg Aug 21 '17 at 0:12
  • $\begingroup$ WOW. That is all I have to say, @MichaelRozenberg. Well done! $\endgroup$ – bjcolby15 Aug 21 '17 at 1:12
  • $\begingroup$ Beautiful...... $\endgroup$ – George N. Missailidis Aug 21 '17 at 7:39
  • $\begingroup$ @GeorgeN.Missailidis It gets the job done, and that is a merit in on itself, but I wouldn't call it an especially beautiful proof :D $\endgroup$ – cirpis Aug 21 '17 at 9:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.